The adoption of interorganisational information systems by South African firms: a technological, organisational and environmental perspective - Mkhize, Zamambo (My University, 2017)
Interorganisational information systems (IOIS) are automated systems which allow one or more firms to connect to their suppliers or customers in order to exchange data and information. Previous literature has suggested that the adoption of interorganisational information systems presents several benefits and challenges. IOIS is assumed to offer organisations the capability to improve business processes and provide better working relations with business partners. Despite this advantage that IOIS offers, adoption of IOIS presents complexities such as those associated with compatibility with a firm's IT infrastructure, lack of available skills, and concerns over data security and system failures. Through a review of existing IOIS literature, this study identified that four types of IOISs are available in South African, namely dyadic, multilateral, community, and hub and spoke. In addition, the technological, organisational and environmental (TOE) factors influencing the adoption IOIS were identified. A model exploring the effects of the pre-determined TOE factors on the adoption of IOIS was developed and tested. The TOE framework provided a theoretical contribution and addressed a gap in the literature into the barriers and determinants of the adoption of interorganisational information system (IOIS) across various organisations. A quantitative study was carried out and survey data was collected from a sample of 119 organisations across different sectors in South Africa. Data was collected using a structured questionnaire instrument administered online to a single key informant from each sampled organisation. The results revealed that multilateral IOIS are the most adopted systems while Hub and spoke IOIS are the least used. Furthermore, from the elven technologies which were identified in the literature review, the study revealed that groupware technologies, electronic payment system/online banking, video conferencing and electronic data interchange were the most adopted IOIS technologies within the sampled organisations. Adoption of IOIS was defined in two ways. First, IOIS adoption was measured as the number of implemented IOIS technologies. Second, as the extent which IOIS is used as communication medium with business partners and supports an organisation in decision making, business operation and replaces legacy technologies. Correlation analysis was used to test the model’s hypotheses and multiple regression was used to test the overall TOE model. The results showed that perceived compatibility, competition, and IS technical skill and education and training are most correlated with the adoption of IOIS, where adoption is measured as the extent of IOIS used as communication medium with business partners and used as support within an organisation. Top management support, trading partner pressure and perceived relative advantage of IOIS were also positively correlated with adoption, where adoption is measured as implemented IOIS technologies. Perceived complexity was found to be a barrier to IOIS adoption. This study serves as a guide for assessing factors contributing to interorganisational information system adoption and provides organisations with greater insight into the factors likely to enable and inhibit IOIS adoption. Keywords: IOS, IOIS, Technology-Organisation-Environment (TOE) Framework, information technology, IS department.
Thesis (M.Com. (Information Systems))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2017
Keywords: Management information systems; Business--Data processing; Information technology